Flume studies using medium sand (0.45mm) - Simons, D. B., author; Richardson, E. V., author; Albertson, M. L., author; USGS, publisher (Colorado State University. Libraries, 1961)
The results pertaining to the progress during the first year of a comprehensive study of fluvial hydraulics, specifically roughness in alluvial channels, are presented. The report is based on the data collected by using a recirculating rectangular flume of adjustable slope, 8 feet wide, 2 feet deep, and 150 feet long with an alluvial bed of sand approximately 0. 7 foot deep. A typical river sand has been utilized. Its median diameter, d, is 0.45 mm and its relative standard deviation, σ, is 1.60. A total of 45 runs have been completed over a range of bed roughness forms extending from the plane bed with no movement to antidunes. In order to achieve this range, the discharge was varied from 2 to 21 cubic feet per second, the average velocity was varied from 0.5 to 7 feet per second, the average depth of flow was varied from 0.3 to 1.0 foot, and the slope of water surface was varied from 0.00014 to 0.01. Other variables measured included: water temperature, bed roughness, suspended sediment load, and total sediment load. Terms describing channel roughness were formulated and tested based on the data collected. The results indicate, as one possibility, that the Chezy coefficient of discharge in dimensionless form C/√g is a function of parameters involving the Froude number, viscosity of fluid, fall velocity, specific weight of the sediment, median diameter of the sediment particles and slope of the water surface. The various expressions presented were formulated on the fundamental concepts of fluid mechanics, dimensional analysis, and a detailed study of the variations of the variables measured. In the two regimes of flow the following forms of bed roughness were observed. For tranquil flow regime: plane bed without movement, ripples, dunes and transition from dunes to rapid flow forms. For rapid flow regime: plane bed with movement, standing sand waves, and antidunes. These forms of bed roughness are discussed and defined in various relationships. Other data of both a laboratory and a field nature were combined with the flume data to develop a graphical relationship in which the form of bed roughness is related to size of bed material.
CER58DBS2.
Keywords: Suspended sediments -- Measurement; Sedimentation and deposition -- Research